Nomination and hibah issues in Malaysian takaful (Islamic insurance) industry - Salman, Syed Ahmad; Htay, Sheila Nu Nu (Jai hind Education Society, Pune., 2013)

(untitled)
The Takaful industry is quite new and currently expanding compared to the conventional insurance industry. There are many issues yet to be resolved. One such issue is the issue of nomination and hibah. The objective of this paper is to look into the issue of nominations and the relevance of Hibah to the nomination in the Takaful industry in Malaysia. The study concludes and proposes some recommendation for certain issues in nominations and Hibah in Takaful Industry.